TI_GERICHTE 16.2004.113 vom 16. November 2004 , appalto - convenuto assente all'udienza - nuove allegazioni in cassazione - TI Tribunale d'appello (2004)
appalto - convenuto assente all'udienza - nuove allegazioni in cassazione